Classification of disease severity in retinitis pigmentosa. Issue 11 (31st January 2019) - Iftikhar, Mustafa; Lemus, Marili; Usmani, Bushra; Campochiaro, Peter A; Sahel, José Alain; Scholl, Hendrik P N; Shah, Syed Mahmood Ali
Abstract : Aim: To develop a simple and easily applicable classification of disease severity in retinitis pigmentosa (RP). Methods: This is a retrospective cross-sectional study. Visual acuity (VA), visual field width (VF) and ellipsoid zone width (EZ) were obtained from medical records of patients with RP. A scoring criterion was developed wherein each variable was assigned a score from 0 to 5 depending on its distribution. The cumulative score (from 0 to 15) was used to classify disease severity from grade 0 to 5. The scores were correlated with each other and the final grade. The grades were then correlated with age and disease duration. Results: The median age (range) of patients (n=93) was 55 (12–87) years, 51% were female, 70% had been diagnosed within 10 years, and 50% had autosomal recessive disease. Most eyes (n=181) at least had a VA of 20/40 (67%), a VF of 20° (75%) and an EZ of 5° (76%). All scores were correlated with each other (r=0.509–0.613; p<0.001 for all) and with the final grade (r=0.790–0.869; p<0.001 for all). Except for grade 0 (5%), all grades were evenly distributed: 21% for grade 1, 23% for grade 2, 22% for grade 3, 17% for grade 4 and 12% for grade 5. Grades were correlated with both age (r=0.252; p<0.001) and disease duration (r=0.383; p<0.001). Conclusions: We present a simple, objective and easy to use disease severity classification for RP which can be used to categorise and compare patients.